The influence of evaluative right/wrong feedback on phonological and semantic processes in word learning - Krishnan, S; Wood, H; Bishop, D; Watkins, K (Royal Society, 2018)
Feedback is typically incorporated in word learning paradigms, in both research studies and commercial language learning apps. While the common-sense view is that feedback is helpful during learning, relatively little empirical evidence exists about the role of feedback in spoken vocabulary learning. Some work has suggested that long-term word learning is not enhanced by the presence of feedback, and that words are best learned implicitly. It is also plausible that feedback might have differential effects when learners focus on learning semantic facts, or when they focus on learning a new phonological sequence of sounds. In this study, we assess how providing evaluative (right/wrong) feedback on a spoken response influences two different components of vocabulary learning, the learning of a new phonological form, and the learning of a semantic property of the phonological form. We find that receiving evaluative feedback improves retention of phonological forms, but not of semantic facts.